THE WILLINGNESS OF SOCIAL WORKERS TO THE SOCIAL-PEDAGOGICAL SUPPORT FAMILIES WITH COMPLEX LIFE CIRCUMSTANCES - Pyesha, Iryna V.; Solyanyk, Maryna H. (Educological discourse, 2014)
The article is devoted to the problem of socio-pedagogical support families who find themselves in difficult circumstances. This paper formulates the definition of the term "readiness specialist social services to socially-pedagogical support families who find themselves in difficult circumstances" and defined criteria, indicators and levels of readiness specialist social services to socially-pedagogical support families who find themselves in difficult circumstances.